Pro SharePoint 2003 Development Techniques - Bruggeman, Nikander (Apress, 2012)
SharePoint Products and Technologies 2003 has been around for a couple of years now. We like the product and have been working with SharePoint technology since the beta release of SharePoint Portal Server 2001. Lately, we had the feeling that there was room for a new book about SharePoint Products and Technologies 2003: a book that describes contemporary development techniques for doing SharePoint development. This book comes at a perfect time. It could not have been written one or two years earlier, because it describes brand-new technology; and in one or two more years SharePoint 2007 will hit the market and be slowly adopted by companies. The result of this thinking is the book you are holding in your hands.